Tumor-associated metabolic and inflammatory responses in early stage non-small cell lung cancer: Local patterns and prognostic significance. (August 2018) - Millares, Laura; Barreiro, Esther; Cortes, Roldan; Martinez-Romero, Anabel; Balcells, Cristina; Cascante, Marta; Enguita, Ana Belen; Alvarez, Carlos; Rami-Porta, Ramón; Sánchez de Cos, Julio; Seijo, Luis; Monsó, Eduard; et al.
Highlights: High metabolic and inflammatory activity characterizes early stage NSCLC. Pentose phosphate pathway proteins are overexpressed in adenocarcinoma. PDL1 is identified in >15% of early stage lung adenocarcinomas. High levels of IL-1β in NSCLC tissue are associated with 3-year mortality in ADC. Abstract: Introduction: Non-small cell lung cancer (NSCLC) patients diagnosed in early stage and surgically-treated have five-year mortality rate >20%. The identification of biomarkers able to predict progression and death may help to identify patients needing closer follow-up. Methods: A retrospective cohort of early-stage surgically-treated NSCLC patients enrolled in the International Association for the Study of Lung Cancer (IASLC) Staging Project was created, and tissue Microarrays (TMAs) were constructed with tumor and non-tumor lung tissue. Pentose phosphate pathway (PPP) proteins (transketolase [TKT] and transketolase-like 1 [TKTL1]), inflammatory markers (cyclooxygenase-2 [COX-2], tumor necrosis factor alpha [TNF-α], interleukin 1 beta [IL1β], nuclear factor kappa-light-chain-enhancer of activated B cells [NFκB]-p65 and antigen Ki-67), and programmed death-ligand 1 (PDL1) were measured by immunohistochemistry. Results: NSCLC patients with adenocarcinoma (ADC) or squamous cell carcinoma (SCC) were included in the study (n = 199). TKT and TKTL1 were significantly higher in ADC than in non-tumor tissue (p < 0.001). Higher values were also observed in NSCLC for all the inflammatory markers, with figures >30% above those of non-tumor tissue (p < 0.001). PDL1 analysis showed a higher percentage of positivity in ADC than in non-tumor tissue (p < 0.001). Multivariate Cox proportional hazards modeling confirmed that high IL1β level in tumor tissue was independently associated with 3-year mortality in NSCLC [HR = 2.05, 95% CI (1.1–3.7), p = 0.019], a relationship driven by ADC subtype. Conclusion: This study confirms an increase in metabolic activity and an inflammatory response in tumor tissue of early stage NSCLC, and a significant relationship between high levels of IL1β in the tumor and poor prognosis in ADC.